Bio‐Based Hybrid Catalysts for the Synthesis of Pharmacologically Active Xanthenes. Issue 11 (14th March 2023) - Karimi Askarani, Hajar; Karimi Zarchi, Mohammad Ali; Fatemeh Mirjalili, Bi Bi; Bamoniri, Abdolhamid
Abstract: We synthesized an efficient bio‐based nano‐catalyst, – Fe3 O4 @nano linear dextrin/Sb +5 (Fe3 O4 @NLD/Sb +5 ) – from nano linear dextrin and antimony pentachloride via straightforward steps. The nano‐catalyst was used to synthesize solvent‐free 14‐aryl‐14 H ‐ dibenzo[ a,  j ]xanthene derivatives based on 2‐aminobenzimide and different aldehydes. The synthesized nano‐catalyst bears many critical advantages: nontoxicity, biocompatibility, affordability, easy work‐up method, environmentally friendliness, and high yields, as well as being solvent‐free and operable under green conditions. Abstract : We synthesized an efficient bio‐based nano‐catalyst, – Fe3 O4 @nano linear dextrin/Sb +5 (Fe3 O4 @NLD/Sb +5 ) – from nano linear dextrin and antimony pentachloride via straightforward steps. The nano‐catalyst was used to synthesize solvent‐free 14‐aryl‐14 H ‐ dibenzo[ a,  j ]xanthene derivatives based on 2‐aminobenzimide and different aldehydes.